HUBUNGAN POLA MENYUSUI DENGAN PERKEMBANGAN BAYI USIA 6 â 12 BULAN - Mumtaz, Suci Hati; Agrina, Agrina; Dewi, Ari Pristiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Breastfeeding is one of the first early childhood development interventions, in order to prepare children for a prosperous future. This research aimed to determine the relationship between breastfeeding patterns with infants aged 6-12 months development at Payung Sekaki Health Center area, Pekanbaru City. A cross sectional correlation research design was used for this study. Purposive sampling techniques were used to a total of 85 mothers with 6-12-month-old infant. Questionnaire and a sheet of the Denver Development Screening Test (DDST) are used as child developmental assessment. Univariate and bivariate analysis with chi-square test showed that 48.2% infants were partially breastfed and 63.5% had a normal development. The results of bivariate analysis showed that the majority of infants with normal development had an exclusive breastfeeding pattern (85.0%) and predominantly breastfed babies are up to 83.3% with p value (0.000) <Î± (0.05). It can be concluded that there is a connection between breastfeeding pattern and the development of infants aged 6-12 months. It is hoped that health workers can increase their active role by providing health education on the importance of exclusive breastfeeding as well as conducting monitoring activities on infant development. Â Keywords: Breastfeeding Pattern, DDST, Infant Development